Justice League Dark. Volume 2, Lords of order - Tynion, James, IV (Justice League Dark, 2019)
"Wonder Woman and the Justice League Dark are in a race against time as the Otherkind close in on the magical community! The world's magic is fading, and new enemies have appeared to take advantage of Earth's weakness. Doctor Fate has assembled the Lords of Order, trapping the magical community on Earth. In order to save magic, the Justice League Dark must escape Doctor Fate's snares and fight the Otherkind. But can they do all of that without calling on even more dangerous powers for assistance?"--